Investigation into the effects of non-motorised transport facility implementations and upgrades in urban South Africa - Baufeldt, Jennifer (Department of Civil Engineering, 2016)
Non-motorised Transport (NMT), as a mode of transport, is beneficial and sustainable for both developing and developed countries. In urban areas of South Africa, NMT users face various challenges that reduce the attractiveness of selecting NMT trips. Two main concerns are the high risk of injury (or death) and the inadequate provision of NMT facilities, making NMT trips inefficient and dangerous. One strategy of addressing these two challenges is implementing NMT facilities that provide safe, convenient and comfortable routes for NMT users. By improving the quality of NMT facilities and increasing the number of NMT facilities available to NMT users, the quality of service that NMT users experience will increase, while at the same time reducing the levels of concerns regarding safety of NMT trips. These changes should result in fewer NMT fatalities and injuries, and consequently, increase the number and quality of NMT trips. While research in other countries has shown that NMT facilities do indeed have these impacts on NMT trips and NMT fatalities and injuries, limited or no research has been conducted to shows that NMT facilities have similar effects in the urban areas of South Africa. This research, therefore, aims to fill this gap in the literature, by investigating the effects that NMT facilities and implementations have in case study areas in urban South Africa. To investigate the impact that NMT facilities have, in urban areas of South Africa, various investigations and case study infrastructure assessments were carried out. A mixed-methods multi-case study research approach was adopted, in order to combine all the various investigations within one research approach. After identifying the NMT facility implementations that had been implemented, a number of case study and control areas were defined. Data regarding the NMT fatalities and injuries in these areas was then identified and used to calculate the trends within the case study areas and the control areas. Additionally, data from the National Household Travel Surveys (NHTS, 2003 and 2013) helped to determine the changes in the number of NMT trips on a provincial level, as well as within the case study and control areas within Cape Town. The last part of the research, used the information, of where the NMT facility implementations took place, alongside infrastructure assessments to determine whether the quality of the NMT facilities had been improved or not. The findings of all the investigations and assessments were then discussed in a SWOT analysis, which could be used in future decisions regarding the implementations of NMT facilities. Results of the investigations carried out in this research indicate that NMT facilities do have significant impacts on improving the levels of safety for both pedestrians and cyclists in urban South African settlements. Furthermore, the results of the investigations and assessments show that the quality of service for NMT users will also increase through improvements to the NMT facilities.